2023
DOI: 10.1007/s40520-023-02412-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity plays a crucial role in multidomain intervention for frailty prevention

Abstract: Background and Aims Taiwan is one of the most rapidly aging countries worldwide. Both physical activity and frailty affect older adults, and multidomain interventions prevent frailty. This study investigated the associations between physical activity, frailty, and the effects of multidomain intervention. Methods This study enrolled individuals aged 65 years or older. The physical activity level was assessed using the Physical Activity Scale for the Elderly (PASE). Enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Our study expands on previous studies that have reported improvement in physical function, frailty, and reduction in inflammation using behavioral lifestyle interventions (ie, diet and physical activity). 19 - 21 A review article investigated the effects of lifestyle interventions and reported improvement in proinflammatory cytokines, such as TNF-α and IL-6 (important mediators of inflammaging). 22 Our results support this data by showing an association between intentional weight loss prescribed through our behavioral intervention and significant improvements in several inflammatory cytokines and frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Our study expands on previous studies that have reported improvement in physical function, frailty, and reduction in inflammation using behavioral lifestyle interventions (ie, diet and physical activity). 19 - 21 A review article investigated the effects of lifestyle interventions and reported improvement in proinflammatory cytokines, such as TNF-α and IL-6 (important mediators of inflammaging). 22 Our results support this data by showing an association between intentional weight loss prescribed through our behavioral intervention and significant improvements in several inflammatory cytokines and frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Another research also found that physical inactivity was a factor strongly associated with ADL and IADL functional limitations in older Korean adults [ 30 ]. The contribution of physical activity to functional impairment may be mediated by a positive effect on muscle strength [ 31 ]. Another supposed mechanism is related to reduced inflammation biomarkers, such as C-reactive protein (CRP) and interleukin-6 (IL-6) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, providing adequate sleep security is an effective strategy to reduce frailty in older adult T2DM patients. Furthermore, lifestyle modifications, appropriate diabetes management, and increased social interaction may help to reduce frailty among older adult T2DM patients with poor sleep quality ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%